Trypsin: A Member Of The Serine Protease Enzyme Isolated From Fusarium oxysporum and Fusarium sp. - Punjungsari, Tyas Nyonita (El-Hayah:Jurnal Biologi, 2024)
Trypsin/Porcine enzyme is widely used in the vaccine manufacturing industry, but due to its non-halal source (intestine of Baby Sus scrofa), it needs an alternative enzyme that has the same characteristics but is sourced from halal things. Fusarium sp. and Fusarium oxysporum are thought to have the ability to produce protease enzymes similar to Trypsin from pigs, which is a natural part of their infection system to cultivated plants. This study was conducted to isolate and characterize enzymes isolated from Fusarium oxysporum and Fusarium sp. Enzyme isolation was carried out using ammonium sulfate precipitation technique. Enzyme characterization using uv-vis spectrophotometer method by making variations of pH, temperature and type of substrate (specific gravity of substrate). Novel Enzyme Trypsin from Fusarium oxysporum isolate has optimum pH 7, optimum temperature 30oC, Vmax 8.183 mM/s and Km 0.9091 mM. Novel Enzyme Trypsin from isolate Fusarium sp. has an optimum pH of 7.5; optimum temperature of 30oC, Vmax 6.911 mM/s and Km 0.6192 mM.